Designing novel morphologies of l-cysteine surface capped 2D covellite (CuS) nanoplates to study the effect of CuS morphologies on dye degradation rate under visible light. Issue 24 (8th June 2020) - Iqbal, Shahid; Bahadur, Ali; Anwer, Shoaib; Shoaib, Muhammad; Liu, Guocong; Li, Hao; Raheel, Muhammad; Javed, Mohsin; Khalid, Bilal
Abstract : Novel CuS@l -Cys NPs are designed by a hydrothermal route. The effects of synthetic parameters on the morphologies of CuS@l -Cys NPs were investigated. CuS@l -Cys NPs exhibit an enhanced dye degradation rate under visible light. Abstract : Pure self-assembled l -cysteine stabilized covellite nanoplates (CuS@l -Cys NPs) with the best control over size, phase purity structure, morphology, and electrochemical properties were synthesized using a facile, template-free hydrothermal route. The effects of temperature (100–180 °C), reaction time (8–24 h), pH of reaction medium (7–14), concentration of base (0.1–2.4 mL NH3 ) and concentration of thiourea (1–4 mmol) on the morphologies of CuS@l -Cys nanoplates were studied. The photocatalytic performance of CuS@l -Cys NPs under visible light was studied using methyl orange (MO) as a model dye. CuS@l -Cys NPs were reused successfully for the photodegradation of dye due to the recycling ability of CuS@l -Cys NPs. The hydroxyl radicals (˙OH) generated by CuS@l -Cys NPs were detected using terephthalic acid (TA) as a probe molecule through the photoluminescence (PL) technique. The successful capping of l -Cys on the surface of CuS NPs was confirmed by FTIR spectroscopy. The BET surface areas of the hexagonal CuS@l -Cys NPs and oblong CuS@l -Cys NPs were measured to be 11.87 and 5.66 m 2 g −1, respectively. The optical band gaps of the hexagonal CuS@l -Cys NPs (2.0 eV) and oblong CuS@l -Cys NPs (2.04 eV) were determined according to direct bandgap calculations. These results support the presence of hexagonal CuS@l -Cys NP catalysts as efficient accelerators of the photodegradation of MO. Furthermore, the l -cysteine (l -Cys) protective layer could efficiently alleviate the photocorrosion of CuS, giving rise to excellent stability. The high photocatalytic activity of the hexagonal CuS@l -Cys NPs can be ascribed to the reduction of photoinduced electron–hole pair recombination and high specific surface area, as confirmed by BET for other representative samples.